Landscapes with archaeological monuments: the case of the Nasca and Palpa lines and geoglyphs - Bolaños Baldassari, Aldo Fernando (2022)
The Nasca and Palpa lines and geoglyphs are located on the desert coast of Peru, 450 km south of Lima. They are inscribed as cultural landscapes on the UNESCO World Heritage List. We analyzed the problems, threats and ways in which the landscape and archaeological monuments of the site are affected by urban growth, agricultural expansion, infrastructure construction, social needs and economic factors related to land use. The loss of natural and cultural landscape values in Nasca was also documented. This article aims to propose solutions for the protection of outstanding universal values (OUV), through the use of landscape treatment units that integrate the future regulation of the heritage area to the existing territorial dynamics.